Examination of the Binding Forms of Cu, Zn, Pb and Cd - Molnár Sz., Katalin (Acta Agraria Debreceniensis, 2003)
Cu, Zn, Pb and Cd binding forms were examined on brown forest soil with clay illuviation, on clcareous chernozem and on meadow soil type. We applied one metal ion and the mixture of all at two different concentrations on the soils. Our results show all the four metal ions significantly bound to the mobile fraction on brown forest soils, while on calcareous chernozem and on meadow soil type they were mainly in other fractions. The higher heavy metal load and the presence of other metal ions increased the ratio of the mobile binding form.